Sistema de custeio no preço de venda (SCPV): análise dos resultados em pequenas e médias empresas industriais da região metropolitana da serra gaúcha - Schneider, José Inácio (Universidade do Vale do Rio dos Sinos, 2016)
This study presents and compares different costing systems observed in the surveyed companies that use the apportionment of indirect costs and indirect expenses in a linear manner and usually without considering the reality of each product and the market itself. In this context, the overall objective was to analyze the results of the implementation of the Costing System in Sales Price (CSSP), using a costs matrix that considers the distribution of indirect costs and fixed expenses in small and medium-sized industrial enterprises through an apportionment reference that parameterizes the average monthly sales at market value of each product. This study also contextualizes and provides a cost structure in a format similar to the Income Statement (IS), using as main source of information the accounting data and financial controls of the companies, simplifying the operation and separating from the bureaucratic reality, which is observed in most companies and complicates the measurement of the costs and the correct establishment of sales price. The study includes the results of active research applied to the deductive and exploratory method with the gathering of bibliographic and documentary data through quantitative and qualitative analysis. This study was developed and based on information from seven small and medium industrial enterprises in the metropolitan region of Serra Gaucha, which are involved with different activities and are located in three municipalities of greater economic importance of the area. Three items considered to be most representative in operating income for the calculation of costs and results analysis were established. The obtained and analyzed results allow us to conclude that the objectives of this study were fully achieved, It was consolidated the Costing System in Sales Price (CSSP) with the reference apportionment for the distribution of indirect costs and expenses, through a cost matrix that follows the logic and structure of the DRE. Reinforcing the idea that cost is a matter of accounting and financial nature and that the sale price should follow the logic of the market.
Keywords: Gestão de custos; Referencial de rateio; Preço de venda; Sistema de custeio; SCPV; Cost management; Apportionment reference; Sale price; Costing system; CSSP; ACCNPQ::Ciências Sociais Aplicadas::Administração